Procedural aspects of the witnesses of witness as a source of evidence - Rohatynska, Nina; Verbovetska, Olha (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The article deals with the features of witness testimony as sources of evidence in the procedural aspect. The question of the place of testimony of witnesses among other sources of evidence is considered. Attention is drawn to the peculiarities of interrogation of juvenile witnesses in order to obtain truthful testimony, the procedural status of the witness, as well as the procedure for assessing the testimony of a witness as reliable, admissible and sufficient evidence.From the characteristics described in the article, one can identify what procedural features distinguish the testimony of witnesses from other sources of evidence. The first of these is the testimony subject to the participants who play an ancillary role in criminal proceedings, and therefore should not be interested in the outcome of the case. Also, there is no statutory age restriction on the witness testifying. Next: the witness's testimony is documented in the interrogation record. Criminal liability for false statements should also be noted. Yes, a person who has reached the age of 16 is criminally responsible for giving false testimony. And the final is the selection of separate evaluation criteria for both the testimony provided by the witness of the crime and the testimony from other people's words.